Consequences of longer sealed curing on drying shrinkage, cracking and carbonation of concrete. (May 2017) - Samouh, Hamza; Rozière, Emmanuel; Wisniewski, Vincent; Loukili, Ahmed
Abstract: The influence of sealed curing on long-term drying behaviour and durability of concrete is investigated in this experimental study. Two concretes were cured for 16 h, 24 h, 48 h, and 1 month then exposed to drying at 20 °C and 50% RH. Mass-loss, total and autogenous shrinkage were monitored. Hydration and microstructural development were studied by isothermal calorimetry and mercury intrusion porosimetry. The drying depth was assessed to quantify the heterogeneity of concrete specimens exposed to drying. The carbonated depth was measured after 6 months, 1 year and 4 years. Longer sealed curing allowed better hydration of cement and reduced long-term water loss. The curing duration significantly influenced the total and drying shrinkage magnitudes. Maximum values were found experimentally and numerically between 24-hour and 48-hour curing. The shrinkage-induced cracking sensitivity was also affected; the shortest sealed curing duration resulted in the lowest cracking index. Linear correlations were found between five properties: compressive strength and degree of hydration at exposure, carbonated depth, median pore diameter, and drying depth. These indicators can be used to optimize the durability of concrete. Sealed curing should be as long as possible to allow hydration of cementitious materials, to minimize drying depth, and to maximize the resistance to carbonation. However, drying shrinkage shows a pessimum; this should be taken into account in the design of durable concrete cover.